A Numerical Design of Marine Current for Predicting Velocity and Kinetic Energy - Parabelem Tinno Dolf Rompas; Heindrich Taunaumang; Ferry Johnny Sangari (Institute of Advanced Engineering and Science, 2017)
One of marine current power plant equipment is turbine. In the design of marine current turbines required variables such as velocity and kinetic energy. This paper presents numerical study on a numerical design of marine current for predicting velocity and kinetic energy in the Bangka strait, North Sulawesi, Indonesia that developed from Yaxum/3D model. This study includes the simulation of velocity and kinetic energy distributions at low and high tide current conditions by two flow rates of 0.1 and 0.3 Sv respectively. The numerical method used to design computational program. Semi-implicit finite difference method used to 3D shallow water flow. It found distributions of velocity and kinetic energy at high tide current condition greater than low tide current condition. The future, these results will be developed in marine current power plant project in the Bangka strait, North Sulawesi, Indonesia.